2010
DOI: 10.1111/j.1744-7976.2009.01161.x
|View full text |Cite
|
Sign up to set email alerts
|

Ecological Goals and Wetland Preservation Choice

Abstract: "Canada's multilayered wetland policies promote the preservation of "significant" wetlands, but the criteria for identifying these wetlands are not clearly defined partially because wetlands are a source of multiple ecological outputs, such as abating sediment and providing wildlife habitat. This study adapts a GIS-based, hydrologic, and economic model to examine the trade-offs between agricultural interests and ecological benefits in the Eramosa Watershed, located in southwestern Ontario, Canada. While preser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 29 publications
(28 reference statements)
0
9
0
Order By: Relevance
“…This study builds upon previous examinations of the trade‐offs involved in wetland drainage (Leitch ; Danielson and Leitch ; van Vuuren and Roy ; De Laporte et al ) by considering the Saskatchewan context, including NAWMP implementation goals. It builds on previous analyses of Saskatchewan wetland economics (van Kooten and Shmitz ; van Kooten , ; Cortus ; Cortus et al ) by incorporating site‐specific GIS information, an alternate evaluation of nuisance costs, and the consideration of universally applicable drainage permits in the prairie context.…”
Section: Introductionmentioning
confidence: 89%
See 2 more Smart Citations
“…This study builds upon previous examinations of the trade‐offs involved in wetland drainage (Leitch ; Danielson and Leitch ; van Vuuren and Roy ; De Laporte et al ) by considering the Saskatchewan context, including NAWMP implementation goals. It builds on previous analyses of Saskatchewan wetland economics (van Kooten and Shmitz ; van Kooten , ; Cortus ; Cortus et al ) by incorporating site‐specific GIS information, an alternate evaluation of nuisance costs, and the consideration of universally applicable drainage permits in the prairie context.…”
Section: Introductionmentioning
confidence: 89%
“…The economics of wetlands have been discussed by a number of authors, including van Vuuren and Roy (), Heimlich et al () and De Laporte et al (). These authors all describe the trade‐offs that exist between private landowners and society.…”
Section: Saskatchewan Wetland Economics and Policymentioning
confidence: 99%
See 1 more Smart Citation
“…He finds that agricultural subsidies raise the marginal value well above payments for wetland preservation and as such farmers have little incentive to preserve wetlands. Laporte et al (2010) find that in the province of Ontario, wetland preservation is hampered by multiple political jurisdictions (federal, province, municipalities, and regional conservation authorities), each of whom govern watersheds. Crepin (2005) makes a useful theoretical contribution by comparing take-it-or-leave-it conservation contracts with uniform contracts.…”
Section: Targeted Conservation Programsmentioning
confidence: 99%
“…While some land‐use decisions yield multiple environmental benefits that are coproduced in tandem (Nelson et al ., ), other management choices can improve one facet of environmental quality at the expense of others (Jackson et al ., ). Research on targeting sites for conservation has shown that when multiple benefits can flow from the land, social welfare and the portfolios of benefits generated can depend critically on which criteria are used to choose sites (Babcock et al ., , ; Zhao et al ., ; Feng et al ., ; De Laporte et al ., ). For example, a program could be established to allow farmers to sell nutrient removal credits associated with installing restored wetlands on portions of their lands.…”
Section: Introductionmentioning
confidence: 99%